Once weekly exenatide: efficacy, tolerability and place in therapy. Issue 10 (24th March 2013) - Wysham, C.; Grimm, M.; Chen, S.
Abstract: Exenatide once weekly is the first glucose‐lowering agent available to patients with type 2 diabetes mellitus (T2DM) which is administered once per week. This long‐acting formulation contains the same active ingredient as exenatide twice daily, except that the exenatide is encapsulated in dissolvable microspheres. Following subcutaneous injection, exenatide once weekly microspheres remain in place under the skin and slowly degrade, releasing active exenatide continuously into circulation. In randomized clinical trials, exenatide once weekly was associated with significant glycaemic improvement and moderate weight loss in patients with T2DM when administered as monotherapy or in combination with a variety of oral antidiabetic agents. Exenatide once weekly also lowered blood glucose more effectively than titrated basal insulin in patients on metformin or metformin plus sulphonylurea background therapy. Gastrointestinal side effects (nausea, vomiting and diarrhoea) were the most common tolerability issues associated with exenatide once weekly administration, but they occurred at lower rates than in patients on other glucagon‐like peptide receptor agonists (i.e., exenatide twice daily or liraglutide). Issues regarding the place of exenatide once weekly in T2DM pharmacotherapy are discussed.